Internationalizing teaching and teacher education for equity : engaging alternative knowledges across ideological borders - Rahatzad, Jubin; Dockrill, Hannah; Sharma, Suniti; Phillion, JoAnn (Emerald Publishing Limited : Information Age Publishing, 2016)
In Internationalizing Teaching and Teacher Education for Equity: Engaging Alternative Knowledges Across Ideological Borders, editors Jubin Rahatzad, Hannah Dockrill, JoAnn Phillion, and Suniti Sharma, present a collection of teacher educators' cross-cultural perspectives on the formation of knowledge through the internationalization of teacher education. Each chapter contributes to ongoing discussions about the process of internationalization in teacher education, and the impact of crossing ideological boundaries on the practice of teaching and teacher education. The varied perspectives that authors offer establish the importance of ideological travel as imperative to preparing internationally competent educators. This collection seeks to engage readers in a variety of critical reflections on the often-presumed benefits of internationalization in teacher education. Through questioning the presumed benefits of globalization as a hegemonic ideology, readers will encounter alternative perspectives that demonstrate the possibility of thinking otherwise. The diverse perspectives available in this book broaden theory, research, and practice, working toward more critical spaces of engagement with the process of internationalization. This collection intends to challenge the maintenance of the dominant ideologies internationally through research from a multiplicity of backgrounds. Each chapter is informed by the authors' commitment to an ethical practice within teacher education for the purpose of constructing equitable social relations, understanding the process of internationalizing teacher education as a social justice movement. Opportunities and challenges within international teacher education are offered to inspire meaningful praxis. Planetary understandings inform readers through critical examinations of theory, research, and practice for the purpose of equitable social and educational transformations.
Keywords: Teachers -- Training of.; Multicultural education.; Education -- Teacher Training & Certification.; Teacher training.; elektronické knihy; electronic books